Trichothecenes Production by Entomopathogenic Fungus Conidiobolus Coronatus - Monika Paszkiewicz; Magdalena Tyma; Marta Ligęza-Żuber; Emilia Włóka; Mieczysława I Boguś; Piotr Stepnowski (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2016)
Entomo pathogenic fungi are of particular interest now as the likely source of a new class of insecticides. This interest stems from the fact that these organisms naturally present in the environment, in most cases selectively affect specific organisms, and metabolites produced by them do not pass into the food chain. Using naturally or artificially introduced organisms to reduce populations of arthropod pests, provide you more than ever the security of the consumers as well as crops and the environment. This is particularly important from the point of view of organic farming, in which there is a need to extend the scope of alternatives against harmful insects. Careful study of the selection of organisms used, as well as the methods of their application are necessary for the efficient and safe prevent losses caused by the pests. Much attention is paid to these issues, with a view to both human health and reducing exposure to unintended infections other living organisms, non-target conservation measures. The aim of this study was to identify toxic metabolites from trichothecene group produced by the parasitic fungus Conidiobolus coronatus. The results of our study allow conclude that the T-2 toxin is present in C. coronatus extract. It was also shown that C. coronatus produced higher amount of trichothecenes when is grown on LB medium. The optimal temperature for production of both T-2 and HT-2 by C. coronatus was 20°C. However, the pH value is the same for grown of C. coronatus mycelium and trichothecenes production. In any of the tested extracts DON and NIV was not detected. Toxicity of C. coronatus homogenates and post-incubation filtrates to G. mellonela larvae and Sf9 cells was also determined.